KAJIAN TINGKAT PENCEMARAN LOGAM BERAT Hg, Cr, Cu dan Zn di SEKITAR PENAMBANGAN EMAS TANPA IZIN (PETI) SUNGAI BATANG KUANTAN KABUPATEN KUANTAN SINGINGI - Irvan Irvan; Bintal Amin; Rahman Karnila (Program Pascasarjana Universitas Riau, 2018)
This research was conducted from March to June 2018 in the waters of Batang Kuantan river subdistrict Gunung Toar. This study aims to analyze the consentration of Hg, Cr, Cu and Zn in water, sediment and scallop (Pilsbryoconcha exilis) and analyze the correlation of consentration Hg, Cr, Cu and Znbetween stasion to water, sediment and scallop in Batang Kuantan River, analyze the pollutan of status heavy metal and to calculate the safety limit in consuming the scallop from the river and effect social economy of society in subdistrict Gunung Toar. Sampling was done at four stasions and analyize of heavy metals concentration was performed by CV-AAS. The result of the study showed that the consentration heavy metals between stasions varied of the river was not significantly different (p>0.05). The average consentration of Hg, Cr, Cu and Zn in water were 0,0904; 0,5910; 0,1342; 1,0210 mg/L and in sediment 0,0380; 0,1525; 0,0090; 0,0409 πg/g, while in scallop 0,0001; 0,0107; 0,0022; 0,1012 πg/g. Havy metals consentration in water, sedimen and scallop shows positive correlations, except Cr. The MPI velue of Batang Kuantan river water was 0,0040 witch was still relatively very low. The heavy metals concentration in water has exceeded the quality standard while in sediment value of (ERL/ ERM) showed logam Hg, Cr, Cu and Zn is still below the value of ERL/ERM. Based on metal in the value of the Geoaccumulation Index (Igeo) logam Hg showed the light contaminated category while Cr, Cu and Zn not yet pollutan category. Based on the calculation of PTWI, it is recommended to consume the scallop from Batang Kuantan river not more than 4480,00 kg/week (Hg), 601,869 kg/week (Cr), 435555,6 kg/week (Cu) and Zn 19358,02 kg/week (Zn). Effect social economi of society to be activity of PETI showed Indexs Participant Respondent (IPR) to environment that is 64,76, economy that is 58,68 and society that is 43,72.